2007
DOI: 10.1093/humrep/del485
|View full text |Cite
|
Sign up to set email alerts
|

Collagen gel contractility is enhanced in human endometriotic stromal cells: a possible mechanism underlying the pathogenesis of endometriosis-associated fibrosis

Abstract: The present findings suggest that the enhanced collagen contractility in ECSCs is associated with myofibroblastic differentiation, the increased expression of fibronectin and the activation of the Rho-ROCK-mediated signalling pathway, all of which may be involved in the pathogenesis of endometriosis-associated fibrosis. These results suggest that the inhibition of the Rho-ROCK-mediated signalling pathway may provide a novel strategy for the treatment of this disease. In addition, our experimental system of ECS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
57
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 52 publications
4
57
1
Order By: Relevance
“…Myosin activity is largely controlled by the phosphorylation of MLC, which can be performed by numerous kinases including the RhoA-regulated kinases ROCK1 and ROCK2 (Olson and Sahai, 2009). Both ROCK and MLC function are required for matrix remodelling by fibroblasts (Gaggioli et al, 2007;Honjo et al, 2007;Yuge et al, 2007).…”
mentioning
confidence: 99%
“…Myosin activity is largely controlled by the phosphorylation of MLC, which can be performed by numerous kinases including the RhoA-regulated kinases ROCK1 and ROCK2 (Olson and Sahai, 2009). Both ROCK and MLC function are required for matrix remodelling by fibroblasts (Gaggioli et al, 2007;Honjo et al, 2007;Yuge et al, 2007).…”
mentioning
confidence: 99%
“…We have established a three-dimensional (3-D) collagen gel culture system with human endometriotic stromal cells as a model of fibrosis formation in endometriosis (5,6). Endometriotic stromal cells were cultured in floating collagen lattices to induce the reorganization and compaction of collagen fibers, resulting in the contraction of the collagen gels.…”
mentioning
confidence: 99%
“…This culture system provided a model of mechanically relaxed tissue with low tensile strength comparable with that in the early stages of development of endometriotic lesions. Using this model, we demonstrated that endometriotic stromal cells cultured in floating 3-D collagen gel exhibit a more enhanced contractile profile and greater ability to differentiate into a myofibroblast phenotype than do normal endometrial stromal cells (5,6). Activation of the Ras homology (Rho)-Rho-associated coiled-coil-forming protein kinase (ROCK)-mediated pathway in endometriotic stromal cells may be involved in this phenomenon (5,6).…”
mentioning
confidence: 99%
See 2 more Smart Citations